Sejarah Jamaah Tabligh: Menelusuri Akar dan Ideologi Gerakan Dakwah - Ibnu Abid (CV. Creative Tugu Pena, 2024)
The aim of this research is to describe the Tablighi Jamaah's da'wah movement. Research results show that the founder of Jamaah Tabligh was a scholar named Muhammad Ilyas bin Muhammad Ismail Al-Kandahlawi. Members of this movement are organized according to how much they contribute and are active in their participation in the movement. The formation of the Tabligh Jamaah was influenced by the local Islamic culture in India. Their preaching movements covered the days of the Prophet and his companions. They claim to be communities that are neutral to religious mazhab, social organizations, and political activities, but still follow the principles of ahlu al-sunnah wa al-jamaah. Their primary purpose is to strengthen the spiritual dimension in the life of every Muslim, both individually and socially. They conveyed the importance of having sincere intentions in spreading religion, while paying attention to the understanding of tasawuf as part of this movement. The typical approach they use is the khuruj, which is based on the 110th verse of Ali Imran's Surah. In Indonesia, the development of the Tabligh Jamaah was very rapid, as evidenced by the increase in the number of members and the widespread religious activity in various regions.